Eye-Hand Coordination Contribution to Shooting Results in Handball Sports - Hidayat, Zulfa; Rasyid, Willadi; Vetra, Yudi (Yayasan Sekora, 2017)
The problem in this research is the low shooting ability of FIK UNP Handball players. While this study aims to determine how much the contribution or contribution of eye-hand coordination (X) to the results of shooting in the handball sport of FIK UNP students (Y). This type of research is a correlation study, namely looking at the relationship between eye-hand coordination on the results of shooting in handball sports of UNP students. The population in this study were 20 people. The sampling technique used in this study was the total sampling technique by making all male student members who took part in the training in the Handball Club of FIK UNP students as samples. The eye-hand coordination data was collected by using the eye-hand coordination test, while the results of the shooting (shooting at the goal) were carried out by a test called the on-target test. The data in this study were analyzed using the Product Moment Correlation formula with a significant level of ? 0.05. The results of the study show that there is a relationship between eye-hand coordination on the results of shooting in FIK UNP Student Handball sport with rcount 0.686> rtabel 0.444 for ? 0.05 and the contribution or contribution between eye-hand coordination variables on shooting results in soccer. the hands of FIK UNP students by 47.1%. Thus eye-hand coordination has a contribution to the results of shooting in the handball sport of FIK UNP students.